Exchange rate expectation, abnormal returns, and the COVID-19 pandemic - Joscha Beckmann; Robert L. Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2022)
This study analyzes the impact of the COVID-19 pandemic on exchange rates based on a comprehensive set of survey forecasts for more than 50 currency pairs. At the first stage, we assess whether the policy to manage the COVID-19 pandemic affects the expected path of exchange rates over the medium and long run. At the second stage, we adopt an event study analysis and identify the occurrences of abnormal returns on foreign exchange markets since the start of the COVID-19 pandemic. Our results suggest the presence of cumulated excess returns that are partly driven by macroeconomic fundamentals for major currencies. However, we find that policy responses to the COVID-19 pandemic have the strongest effect on cumulated excess returns, showing that foreign exchange markets take expected policy effects as an important determinant of future developments into account while expectations for minor currencies react stronger to response policies.
Keywords: F31; F37; G41; 330; Abnormal returns; COVID-19 pandemic; Exchange rates; Expectations; Survey data